Use of fall cone test to estimation of undrained shear strength of soft clay soils from Region San Martin, Peru - Escalaya Advíncula, Miriam Rosanna (2024)
In this research, we seek to experimentally determine the undrained shear strength (Su) of a soft clay soil by unconventional methods in the practice of Peruvian Engineering. The fall-cone test was used, which is a laboratory equipment commonly used to obtain the liquid limit of soils. To calibrate the results, laboratory miniature vane test equipment was used, which provides direct measurement of Su. The study was conducted with thirteen undisturbed samples extracted from the localities of Rioja and Moyobamba in the San Martín region, Peru. As a result, an empirical correlation was obtained that allows the undrained shear strength of these soils to be determines from the fall-cone test. The research concludes that, with adequate calibration, the fall-cone is a reliable tool for determining the undrained shear strength of soft soils. Furthermore, its simple and low-cost execution makes it a quick and economical alternative.